The Analysis of Students' Misconceptions in Shape Material at SMP Negeri 8 Jember - Dwi Apriyanto; Fani Aldilah Rosyadi (Universitas Islam Jember, 2020)
The study aims to determine the type of misconception and the cause of misconception to occur in shape material at SMPN 8 Jember. The research subject amounted to 20 grade 9 students. Data collection techniques using description questions are disseminated online. Data analysis techniques use the grouping criteria of understanding concepts from Renner and Brumby. Based on research that has been conducted through analysis of the results of student answers and interviews conducted online. Then the results obtained show that students of SMPN 8 Jember experience misconceptions in shape material of Error in determining the square including rhombus, error in specifying square including rectangular, error in determining rectangular including the, and error in determining rhombus including kite. Keywords: miskonsepsi, shape